Improvement of Bioremediation Performance for the Degradation of Petroleum Hydrocarbons in Contaminated Sediments - Laura Rocchetti; Francesca Beolchini; Maurizio Ciani; Antonio Dell'Anno (Applied and Environmental Soil Science, 2011)
Microcosm bioremediation strategies were applied to sediments contaminated with hydrocarbons. Experiments were performed in aerobic conditions in a single-step treatment and in a two-step anaerobic-aerobic treatment. In aerobic conditions, either inorganic nutrients or composts were added to the microcosms, while, in the first anaerobic phase of the two-step experiment, acetate and/or allochthonous sulfate-reducing bacteria were used. After the treatment under anaerobic conditions, samples were exposed to aerobic conditions in the presence of compost. In the aerobic treatments, 81% hydrocarbon biodegradation was observed after 43 days in the presence of inorganic nutrients. In aerobic conditions in the presence of mature compost, hydrocarbon biodegradation was 51% after 43 days of treatment, whereas it was 47% after 21 days with fresh compost. The two-step experiment allowed us to obtain a hydrocarbon degradation of 91%, after a first anaerobic step with an inoculum of sulfate-reducing prokaryotes.